Selected Problems of Contemporary Thermomechanics - Winczek, Jerzy (IntechOpen, 2018)
Thermomechanics is a scientific discipline which investigates the behavior of bodies under the action forces and heat input. Thermomechanical phenomena commonly occur in the human environment, from the action of solar radiation to the technological processes. The analysis of these phenomena often requires extensive interdisciplinary knowledge and the application of advanced mathematical apparatus. Thermo-mechanical phenomena are analyzed using analytical and numerical methods. The analytical solution offers a quicker assessment of the searched values and its dependence on the various parameters. Some problems can be solved only by numerical methods, of which the finite element method is commonly used. This book intends to present current trends and methods in solving thermomechanics problems.